Clonal diversity and geographic distribution of methicillin-resistant Staphylococcus pseudintermedius from Australian animals: Discovery of novel sequence types - Worthing, K.; Abraham, S.; Coombs, Geoffrey; Pang, S.; Saputra, S.; Jordan, D.; Trott, D.; Norris, J. (Elsevier, 2018)
Methicillin-resistant Staphylococcus pseudintermedius (MRSP) is an increasingly prevalent pathogen in veterinary medicine. This study examined the molecular epidemiology of clinical MRSP isolated from Australian animals. Clinical staphylococci submitted to all Australian veterinary diagnostic laboratories were collected during 2013 and identified using traditional phenotypic tests and matrix-assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-TOF MS). Phenotypic antimicrobial resistance was determined using broth microdilution and disk diffusion. MRSP isolates were characterized by whole genome sequencing which included identification of the mecA gene. Phylogenetic relationships were inferred by comparison of single nucleotide polymorphisms. Of the 669 S. pseudintermedius isolates collected from dogs, cats and cattle, 77 (11.5%) were MRSP. Nineteen multilocus sequence types (STs) were identified, with most isolates belonging to one of five STs (ST71, ST497, ST316, ST496 and ST45). Phylogenetic analysis revealed that Australian ST71 appears closely related to ST71 from overseas. ST497 and ST496 represented novel sequence types, not previously reported outside Australia. Most other STs were novel and only distantly related to each other. Geographical clustering of STs was observed. All isolates belonging to the five main STs were multi- to extensively- drug resistant while isolates from singleton STs generally had lower levels of antimicrobial resistance. The frequency of ciprofloxacin, trimethoprim-sulfamethoxazole, gentamicin, chloramphenicol and tetracycline resistance varied significantly between STs (p < 0.01). Australian MRSP isolates are phylogenetically diverse, with a mix of previously unreported and well known international MRSP clones that demonstrate geographic clustering and exhibit both multidrug-resistant and extensively drug-resistant phenotypes.